Analisis Penggunaan Aplikasi Kasir dalam Meningkatkan Efisiensi Transaksi pada Usaha Cookies dan Donut - Sari, Amel Putri Fatika; Wardani, Aldita Safira Setya; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
This research aims to explore the application of digital-based cake sales applications among MSME business actors. Using qualitative research methods and case study approaches, this study involves in-depth interviews with 10-15 business actors. Data was collected through interview guides designed to explore respondents' experiences and perceptions regarding the challenges and benefits of using the app in running their business. Data analysis is carried out with a thematic analysis approach, resulting in key themes related to the impact of the application on operational efficiency and customer interaction. The findings of the study show that cake sales applications not only improve the efficiency of the ordering process but also expand market reach for business actors. This research provides recommendations for application developers to continue to innovate based on user feedback to improve service quality and customer satisfaction.